Development of mucoadhesive gelatin-based patches for aphthous ulcers - Lerdsrimongkol, Jiratchaya; Tiyaboonchai, Waree; Kriangkrai, Worawut (Naresuan University Journal: Science and Technology (NUJST), 2023)
Mucoadhesive patches demonstrate considerable promise for the administration of therapeutics targeting oral mucosal diseases. This study employed the solvent casting technique to fabricate mucoadhesive patches and examine the influence of bloom strength variation, plasticizer concentration, gelatin concentration, and alpha-mangostin (α-MN) loading on patch properties. The mucoadhesive patches consisted of a 5% ethylcellulose backing layer, a mucoadhesive layer combining ethylcellulose and gelatin, and a gelatin layer loaded with α-MN. The investigation revealed that augmented gelatin bloom strength correlated with increased puncture strength and elongation at break, but diminished thickness. Owing to its superior characteristics, 300-bloom gelatin was chosen for further examination. The incorporation of glycerin as a plasticizer decreased puncture strength but enhanced elongation at break. An escalation in gelatin concentration from 1% to 7% resulted in amplified patch thickness and puncture strength, with 7% gelatin yielding the most pliable patches. Additionally, the in vitro residence time of the patches rose concomitantly with increasing gelatin concentrations, attributable to heightened interpenetration with mucin chains and the formation of mucoadhesive bonds. Successful α-MN loading into the patches was achieved, exhibiting an actual concentration range of 144.12 ± 27.10 µg to 441.05 ± 94.79 µg. In summary, this study successfully generated mucoadhesive patches exhibiting desirable properties for potential oral mucosal drug delivery applications. These findings serve as a foundation for subsequent optimization and development of mucoadhesive patches to address various oral mucosal diseases. Keywords: mucoadhesive patches, gelatin, α-mangostin, plasticizer, in vitro residence time